Staffing the Hospitals : An Urgent National Need - Great Britain. Ministry of Labour and National Service. (London : Published for the Minister of health, the Secrerary of State for Scotland and the Minister of labour and national service by H.M.S.O., 1945)
1945 1945 1940s 20 pages 6 CODES OF WORKING CONDITIONS 12. The first thing is to be clear what the standards are to be. That is what the intelligent recruit wants to know. To this end the Government and representatives of all the organisations and interests concerned have worked out, in full agreement, two general codes indicating the working conditions and prospects which nursing and hospital domestic work, respectively, should offer as soon as circumstances permit of their being brought into full operation. These codes are appended to this paper and should be carefully studied by all who are interested. 13. From time to time Government and other committees have examined all the aspects of hospital nursing and other hospital work and have made recommendations, many of which have been adopted. In the appended codes most of the recommendations of these committees have been embodied. (A report on mental nursing by the Athlone Committee is now under consideration and will be the subject of a further announcement.) Much of what the appended codes require is already in being in many hospitals. There are other hospitals which fall short of it. What is now proposed is a unified and business-like endeavour to see that the codes become universally accepted standards for hospital employment everywhere, and as soon as possible. 14. A glance at the appended codes will show that their contents cannot all be achieved by a stroke of the pen. In some parts, for example, they involve a substantial call on building labour and materials and that is for the moment out of the question on any big scale. But it will be seen that a very great deal of what is required can be undertaken, where it has not already been, now or in the near future, and with this the Government and the representatives of the various hospital interests intend to press on at once. Moreover, when the proposed National Health Service is set up, it will become the responsibility of every hospital taking part in it to observe these conditions. 15. Perhaps the most important thing to remember about the codes is that most of the prescribed conditions, and in particular those which concern hours of work and off-duty arrangements, become progressively easier to achieve as more workers come into the hospital service. The more recruits, the better the conditions for all. 16. There is, of course, much that cannot appropriately go into these codes, much that is — so to speak — intangible, though highly important. Further, it is not always understood how widely varied are the opportunities and how good are the prospects open to the State Registered nurse. Not only can she choose between curative and preventive work, but within each of these branches there are many different avenues along which she can travel. She can continue with hospital work which offers a wide choice of employments and opportunities of promotion in both general and specialised fields. She can become a midwife ; she can specialise in any of the branches of nursing such as industrial nursing. She can become a district nurse or a private nurse working in the patients' homes. She can take service with the Local Authority as a health visitor, tuberculosis visitor, or school nurse. She can join one of the Nursing Services of the Crown, or she can go abroad to the Dominions or the Colonies. From all these and other fields she can in normal times choose the one most suited to her abilities 126/TG/RES/X/1036A/4